A arte e a arquitetura: proposta de intervenção artística no bloco 1 Universidade Federal do Tocantins - Reis, Douglas Jacinto dos (Universidade Federal do Tocantins, 2021)
This graduation thesis aims to present an intervention proposal in Block 1, located at the Federal University of Tocantins, bringing to light the artistic restlessness through urban art. The intervention starts from the Site Specific concept (art created especially for a given space) where the interaction with the architecture of the place and other elements, shows how art ceases to be an isolated work confined to the paint or gallery and starts to coexist with the space where it is inserted. The work brings the psychology of colors and basic geometry concepts, the intention is to create playful spaces that welcome and inspire users and passers-by, improving the quality of the building's collective spaces and encouraging the creative production of students in the Architecture and Urbanism course, at the same time making art that is public and accessible, stimulating urban kindness.